Modern methods of treatment of patients with high-grade myopia (Journal of Science-Innovative Research in Uzbekistan, 2024)
This review article examines modern views on etiological factors, the pathogenesis of complications and the influence of climatogeographic conditions on the progression of myopia and modern methods of treatment